Evidence for the changes of pituitary volumes in patients with post-traumatic stress disorder. (28th February 2017) - Atmaca, Murad; Ozer, Omer; Korkmaz, Sevda; Taskent, Ismail; Yildirim, Hanefi
Abstract: In pubertal and postpubertal patients with post-traumatic stress disorder (PTSD), significantly greater pituitary gland volumes have been reported. Moving from this point, in the present study, we aimed to investigate pituitary gland volumes in patients with PTSD and hypothesized that volumes of the gland would be structurally changed. Volumetric magnetic resonance imaging of the pituitary gland was performed among sixteen patients with PTSD and fifteen healthy control subjects. We found that the mean volume of the pituitary gland was statistically significant and smaller than that of healthy subjects (0.69±0.08 cm 3 for patient group and 0.83±0.21 for control subjects). Consequently, in the present study, we found that patients with PTSD had smaller pituitary gland volumes than those of healthy controls like other anxiety disorders. It is important to provide support for this finding in future longitudinal investigations. Highlights: In the present study, we aimed to investigate pituitary gland volumes in patients with PTSD and hypothesized that volumes of the gland would be structurally changed. We found that the mean volume of the pituitary gland was statistically significant and smaller than that of healthy subjects. PTSD had smaller pituitary gland volumes than those of healthy controls like other anxiety disorders.